PEMBELAJARAN KONTEKSTUAL BERBASIS AUGMENTED REALITY UNTUK MENGEMBANGKAN VISUALISASI DAN PENALARAN GEOMETRI SISWA SMP - Aldo Arrohim; Syahriani Sirait (MES: Journal of Mathematics Education and Science, 2026)
The purpose of this study was to determine whether there is an effect of implementing Contextual Teaching and Learning (CTL) based on Augmented Reality in developing students’ spatial visualization abilities and geometric reasoning on solid geometry material for eighth-grade students at SMPN 1 Bandar Pulau. This research used a quasi-experimental method with a Two Group Pre-Test and Post-Test research design. The population of this study consisted of all eighth-grade classes, totaling four classes. The research sample consisted of two classes selected through purposive sampling determined by the school. The control class used the CTL learning model, while the experimental class used Augmented Reality-based contextual learning. After the learning process was completed, the post-test results showed that the average score of the experimental class was 71.696 and the control class was 67.048. The results of the t-test obtained t_count = 1.708 > t_table = 1.669, therefore Hₐ was accepted. In addition, this study also used questionnaires to measure students’ perceptions of Augmented Reality-based contextual learning. The questionnaire results indicated that the majority of students gave positive responses toward the use of AR in learning. A total of 42.9% of students strongly agreed and 43.4% agreed that contextual learning with AR made the learning process more interesting, enjoyable, and helpful in understanding solid geometry concepts. Thus, it can be concluded that there is an effect on students’ learning outcomes through the use of Augmented Reality-based contextual learning in developing students’ 3D visualization abilities and geometric reasoning.